Catalytic effects of IMF agreements on foreign direct investment (FDI) inflows in sub-Saharan Africa - Mathebula, Percy (Research of GSB, 2018)
It is customary to postulate that International Monetary Fund (IMF) agreements or arrangements in Sub-Saharan Africa (SSA) will facilitate foreign capital investments or FDI inflows from multinational corporations and or foreign investors. Through empirical observations, and using a two-stage modelling technique, this research tested and examined this hypothesis. It empirically showed that SSA countries that had IMF interventions for the period 1980 to 2015 attracted FDI inflows into their economies. The study rebutted the claim that countries with previous IMF interventions were likely to appeal to multinational corporations (MNCs) or foreign investors and thereby cause the inflow of FDI into Sub-Saharan Africa.